Managing climate change risk in China's agricultural sector: The potential for an integrated risk management framework - Chen, Kevin Z.; Hsu, Claire (Elsevier, 2014)
Climate change poses a serious threat to the future food security of China, which is among the most disaster-prone countries in the world. This paper discusses the implications of climate change for China's agricultural sector. Its main objectives are to identify the agricultural risks associated with climate change, to introduce a conceptual framework for agricultural climate risk management and to enumerate key adaptation strategies, challenges, and recommendations.